"In my home nobody spoke about religion, politics or football": Communicative silences among generations in Argentina and Chile. (August 2020) - Frei, Raimundo
Social silence has been one of the poignant concepts of memory studies, although one predominantly encapsulated by "traumatic" and "denying" approaches. In contrast, this article focuses on broader daily life dynamics of narrating silence to understand mnemonic cultures. By denoting practices of silence, individuals connote underlying regulations about what can be brought to the fore or left "under the carpet." Based on biographical narratives of members of two post-dictatorial generations in Argentina and Chile, I identify five mechanisms which produce silence among generations: fear of talking, a collective template of reconciliation, a lack of repertoires of justification, the control of symbolic boundaries, and patterns of conflict management. Finally, I claim that these mechanisms—or varieties of silence—act more efficiently in Chilean than Argentinean political culture. This might be as a result not only of opposed transitional justice paths but also of different communicative patterns historically rooted.